Análisis Macroeconómico del Derecho - Fernández Salas, José Carlos (2015)
This article analyzes the relationship that Law may have with the ield of macroeconomics, under the premise that Law and Economics has traditionally focused on the relationship between Law and microeconomics. For this purpose, the author makes a summary of the differences between the both ields of economics, and a summary of the tools Law and Economics has collected from them. It is described how the academic coming together between Law and macroeconomics has been driven by the global economic crisis that began in 2008. It is then described how the study and interpretation of legal institutions can consider their macroeconomic context.